Poka-Yoke Integration into Process FMEA - A. Perumal, Puvanasvaran; Jamibollah, N.Jamibollah; Norazlin Nasir, N.Norazlin; Adibah Razali, R. Adibah (AENSI, 2014)
Poka-Yoke and failure mode and effect analysis (FMEA) are methodologies that facilitate process improvement and manufacturing capabilities. Poka-Yoke conceptually fits into the process FMEA (PFMEA). Two integration concepts are proposed by using FMEA and PFMEA. The first concept focuses on the elimination of the cause of defects that is directly linked to the occurrence of the error that creates the defects. The second concept is attributed to the segregation of rejects, which focuses on the effectiveness of the detection system. The control and action taken by an organization will evolve into a foolproof process by integrating Poka-Yoke into the PFMEA. Such an error-free process will drive an organization toward the manufacture of defect-free products. The format of Poka-Yoke PFMEA can guide users who are unfamiliar with the best actions and controls. The integration concepts can be further expanded to cover risks or accidents, particularly in terms of hazard identification, risk assessment, and control. The integration of lean concepts will significantly influence quality improvement and process optimization. This improvement will eventually affect manufacturing cost because lean concepts always focus on waste control, optimization, pull push concepts, and 5S. Lean concepts eliminate the rejects and optimize the overall manufacturing cost.